Sudan question and Ottoman policies against the colonial powers in Eastern Africa - Kiziltoprak, S. (Культура народов Причерноморья, 2004)
European States attended a new kind of competition with the Columbus, Vasco de Gama, Magellan and Drake’s exploration voyages. This competition was among the European powers but the competition area was out of Europe, on the lands of India, Africa and America. The sides were trying to save the lands under their dominance by both diplomacy and wars. After the European powers’ discoveries of marine lines in 15th and 16th centuries, the war in Europe gradually spread out of Europe.